Inspired from AIME problem 6

Geometry Level 5

s = k = 1 45 ( csc 2 ( 2 k 1 ) + 3 ) s = \prod_{k=1}^{45} \left ( \csc^2(2k-1) + 3 \right )

Angles measured in degrees.

If 2 s 1 = m m n 2s-1 = m^{mn} with positive integers m , n m,n and m m is not a prime, find m + n m+n .


The answer is 14.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Lets first make everything into radians,

s = k = 1 45 ( c s c 2 ( 2 k 1 ) π 180 + 3 ) s=\prod _{ k=1 }^{ 45 }{ ({ csc }^{ 2 } } (2k-1)\frac { \pi }{ 180 } \quad +3)

s = k = 1 45 ( c o t 2 ( 2 k 1 ) π 180 + 4 ) s=\prod _{ k=1 }^{ 45 }{ ({ cot }^{ 2 } } (2k-1)\frac { \pi }{ 180 } \quad +4)

If we find a polynomial p(x) whose roots are c o t 2 ( ( 2 k 1 ) π 180 ) { cot }^{ 2 }((2k-1)\frac { \pi }{ 180 } ) all we have to do then is find p(-4).

The expression for tan(nx) is as follows

t a n ( n x ) = ( n 1 ) t a n ( x ) ( n 3 ) t a n 3 ( x ) + . . 1 ( n 2 ) t a n 2 ( x ) + ( n 4 ) t a n 4 ( x ) . . tan(nx)=\frac { \left( \begin{matrix} n \\ 1 \end{matrix} \right) tan(x)-\left( \begin{matrix} n \\ 3 \end{matrix} \right) { tan }^{ 3 }(x)+.. }{ 1-\left( \begin{matrix} n \\ 2 \end{matrix} \right) { tan }^{ 2 }(x)+\left( \begin{matrix} n \\ 4 \end{matrix} \right) { tan }^{ 4 }(x)-.. }

This expression can be obtained quite easily using complex no.s

We observe that for all θ = ( 2 k 1 ) π / 180 \theta =(2k-1)\pi /180
t a n ( 90 θ ) tan(90 \theta) = t a n ( ( 2 k 1 ) π / 2 ) tan((2k-1)\pi /2)

which is undefined

This implies that for these values of θ \theta the denominator for the expression of t a n ( 90 θ ) = 0 tan(90 \theta)=0

So we've got a polynomial in t a n ( θ ) tan(\theta) whose roots are t a n ( ( 2 k 1 ) π / 180 ) tan((2k-1)\pi /180) ,

p ( t a n θ ) = ( 90 0 ) t a n 0 ( θ ) ( 90 2 ) t a n 2 ( θ ) + ( 90 4 ) t a n 4 ( θ ) + . . . p(tan\quad \theta )=\left( \begin{matrix} 90 \\ 0 \end{matrix} \right) { tan }^{ 0 }(\theta )-\left( \begin{matrix} 90 \\ 2 \end{matrix} \right) { tan }^{ 2 }(\theta )+\left( \begin{matrix} 90 \\ 4 \end{matrix} \right) { tan }^{ 4 }(\theta )+...

or p ( c o t θ ) = ( 90 0 ) c o t 90 ( θ ) ( 90 2 ) c o t 88 ( θ ) + ( 90 4 ) c o t 86 ( θ ) + . . p(cot\quad \theta )=\left( \begin{matrix} 90 \\ 0 \end{matrix} \right) { cot }^{ 90 }(\theta )-\left( \begin{matrix} 90 \\ 2 \end{matrix} \right) cot^{ 88 }(\theta )+\left( \begin{matrix} 90 \\ 4 \end{matrix} \right) { cot }^{ 86 }(\theta )+..

or p ( c o t 2 θ ) = ( 90 0 ) c o t 2 ( θ ) 45 ( 90 2 ) c o t 2 ( θ ) 44 + ( 90 4 ) c o t 2 ( θ ) 43 + . . p({ cot }^{ 2 }\quad \theta )=\left( \begin{matrix} 90 \\ 0 \end{matrix} \right) { { cot }^{ 2 }(\theta ) }^{ 45 }-\left( \begin{matrix} 90 \\ 2 \end{matrix} \right) { { cot }^{ 2 }(\theta ) }^{ 44 }+\left( \begin{matrix} 90 \\ 4 \end{matrix} \right) { { cot }^{ 2 }(\theta ) }^{ 43 }+..

Putting x= c o t 2 ( θ ) cot^2(\theta) ,we get p ( x ) = x 45 ( 90 2 ) x 44 + ( 90 4 ) x 43 p(x)={ x }^{ 45 }-\left( \begin{matrix} 90 \\ 2 \end{matrix} \right) { x }^{ 44 }+\left( \begin{matrix} 90 \\ 4 \end{matrix} \right) { x }^{ 43 } = k = 1 45 ( x c o t 2 ( ( 2 k 1 ) π / 180 ) ) =\prod _{ k=1\\ }^{ 45 }{ (x-{ cot }^{ 2 }( } (2k-1)\pi /180))

Putting x = 4 x= -4 ,we get

s s = r = 1 45 ( 90 2 r ) 2 2 r \sum _{ r=1 }^{ 45 }{ \left( \begin{matrix} 90 \\ 2r \end{matrix} \right) } { 2 }^{ 2r }

= 3 90 + 1 2 \frac { { 3 }^{ 90 }+1 }{ 2 }

Hence 2 s 1 = 3 90 = 9 45 2s-1={ 3 }^{ 90 }={ 9 }^{ 45 }

m = 9 , n = 5 m=9,n=5

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...